DFT calculation of the chromyl nitrate, CrO2(NO3)2. The molecular force field - Brandan, Silvia Antonia (2008)
We have carried out a structural and vibrational theoretical study for chromyl nitrate. The density functional theory has been used to study its structure and vibrational properties. The geometries were fully optimised at the B3LYP/Lanl2DZ, B3LYP/6-31G* and B3LYP/6-311++G levels of theory and the harmonic vibrational frequencies were evaluated at the same levels. The calculated harmonic vibrational frequencies for chromyl nitrate are consistent with the experimental IR and Raman spectra in the solid and liquid phases. These calculations gave us a precise knowledge of the normal modes of vibration taking into account the type of coordination adopted by nitrate groups of this compound as monodentate and bidentate. We have also made the assignment of all the observed bands in the vibrational spectra for chromyl nitrate. The nature of the Cr-O and Cr ← O bonds in the compound were quantitatively investigated by means of Natural Bond Order (NBO) analysis. The topological properties of electronic charge density are analysed employing Bader's Atoms in Molecules theory (AIM). © 2007 Elsevier B.V. All rights reserved.